2019
DOI: 10.1002/jhbp.695
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter prospective registration study on laparoscopic pancreatectomy in Japan: report on the assessment of 1,429 patients

Abstract: Background Prospective studies are needed to understand the safety and feasibility of laparoscopic pancreatectomy. The aim of the present study was to describe laparoscopic pancreatectomy currently undertaken in Japan, using a prospective registration system. Methods Patient characteristics and planned operations were registered preoperatively, and then the performed operation and outcomes were reported using an online system. Collected data were also compared between institutions based on their level of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In our study, the RDP group showed a significantly higher SP rate (30.2%) than that of the LDP (6.8%) group in patients with benign and low-grade malignant distal (12). However, LDP still has several technical limitations, such as reduced freedom of motion and narrowed two-dimensional visualization which may impact the surgery results (6,13,14).…”
Section: Discussionmentioning
confidence: 58%
“…In our study, the RDP group showed a significantly higher SP rate (30.2%) than that of the LDP (6.8%) group in patients with benign and low-grade malignant distal (12). However, LDP still has several technical limitations, such as reduced freedom of motion and narrowed two-dimensional visualization which may impact the surgery results (6,13,14).…”
Section: Discussionmentioning
confidence: 58%
“…We used the largest prospective registry available for minimally invasive PD in Japan. Japan has another prospective registry of minimally invasive PDs managed by the Japanese Society for Endoscopic and Robotic Pancreatic Surgery/Japanese Society for Endoscopic Surgery/Japanese Society of Hepato‐Biliary‐Pancreatic Surgery 18 . Although its registration system differs from that of the NCD, there is an overlap in the registration of some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this potential benefit, MIDP is only used in about one‐third of patients, according to a recent analysis of the National Surgical Quality Improvement Program (NSQIP) database 9 . In Japan, a multicenter prospective registration study including 1197 LDPs revealed that postoperative morbidity and 90‐day mortality rates after LDP were 17% and 0.3%, respectively 10 . Thus, LDPs are performed safely in Japan, especially in experienced institutions.…”
Section: Minimally Invasive Distal Pancreatectomy (Midp)mentioning
confidence: 99%
“…The laparoscopic procedure is unsuitable for the reconstruction process of LPD because of the difficulty in adjusting the axis of the forceps to adequate suturing lines of pancreatic or biliary reconstruction. 10 Immature reconstruction substantially leads to postoperative complication such as clinically relevant pancreatic fistula/anastomotic leakage, resulting in prolonged hospital stay and even surgery-related mortality. These situations also apply to OPD.…”
Section: Minimally Inva S Ive Pan Cre Atoduodenec Tomy (Mipd)mentioning
confidence: 99%